Chronic caffeine consumption curbs rTMS-induced plasticity - Megan Vigne; Jamie Kweon; Prayushi Sharma; Benjamin D. Greenberg; Benjamin D. Greenberg; Linda L. Carpenter; Linda L. Carpenter; Joshua C. Brown; Joshua C. Brown; Joshua C. Brown (Frontiers in Psychiatry, 2023)
BackgroundCaffeine is a widely used psychostimulant. In the brain, caffeine acts as a competitive, non-selective adenosine receptor antagonist of A1 and A2A, both known to modulate long-term potentiation (LTP), the cellular basis of learning and memory. Repetitive transcranial magnetic stimulation (rTMS) is theorized to work through LTP induction and can modulate cortical excitability as measured by motor evoked potentials (MEPs). The acute effects of single caffeine doses diminish rTMS-induced corticomotor plasticity. However, plasticity in chronic daily caffeine users has not been examined.MethodWe conducted a post hoc secondary covariate analysis from two previously published plasticity-inducing pharmaco-rTMS studies combining 10 Hz rTMS and D-cycloserine (DCS) in twenty healthy subjects.ResultsIn this hypothesis-generating pilot study, we observed enhanced MEP facilitation in non-caffeine users compared to caffeine users and placebo.ConclusionThese preliminary data highlight a need to directly test the effects of caffeine in prospective well-powered studies, because in theory, they suggest that chronic caffeine use could limit learning or plasticity, including rTMS effectiveness.